1992
DOI: 10.1111/j.1600-0471.1992.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Excavations at ed‐Dur (Umm al‐Qaiwain, U.A.E.)

Abstract: The results of seven weeks’research in 1989 by a Belgian team from Gent University at ed‐Dur, in the Emirate of Umm al‐Qaiwain, are presented. Excavations were continued in the southern part of the site. A fourth altar was found near the temple (area M); graves were excavated in other areas (areas N and AT). A large, undisturbed, semi‐subterranean tomb with a barrel‐vault and enclosure (area AV) was also discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Because of their high number and the presence of a ceramic support resembling an incense burner, Lombard calls these figurines votive (10). Significantly, in the vicinity of ed-Dur altar 1, three similar objects were found that Haerinck has interpreted as incense burners, one of which still contained the remains of incense in the bowl (11). Figurine 1 also shows close parallels with human figurines found at Tell Khazneh on Failaka, where over 280 fragmentary and complete figurines were discovered, accounting for over one quarter of the site's material inventory (12).…”
Section: Figurinementioning
confidence: 98%
“…Because of their high number and the presence of a ceramic support resembling an incense burner, Lombard calls these figurines votive (10). Significantly, in the vicinity of ed-Dur altar 1, three similar objects were found that Haerinck has interpreted as incense burners, one of which still contained the remains of incense in the bowl (11). Figurine 1 also shows close parallels with human figurines found at Tell Khazneh on Failaka, where over 280 fragmentary and complete figurines were discovered, accounting for over one quarter of the site's material inventory (12).…”
Section: Figurinementioning
confidence: 98%
“…Although the style of the ed‐Dur bowl is somewhat naïve and comparisons should therefore be considered with caution, the peculiar bulbous way in which the horses’ noses are fashioned does present a striking parallel with the horse‐shaped spouts on bronze vessels from ed‐Dur and Mleiha (Haerinck, : pls. 93, 116–117; Jasim, Uerpmann & Uerpmann, : 130) (Fig.…”
Section: Concluding Remarks On Date and Provenancementioning
confidence: 99%
“…A bronze vessel with a horse spout from a tomb at ed‐Dur (after Haerinck, : pls. 93 & 117) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Concluding Remarks On Date and Provenancementioning
confidence: 99%
“…Ed-Dur is a coastal site in the United Arab Emirates covering as much as 800 ha, although occupation within that area was probably a patchy mixture of tombs and low-density settlement (292). There are some traces of much earlier settlement, but the main site appeared in the late first century BC or the first century AD and achieved its maximum extent during the first and early second centuries AD (293). Amongst the grave goods the site has yielded plentiful evidence of trade with the Roman world as well as with South Asia, Iran and Mesopotamia.…”
Section: Large Sitesmentioning
confidence: 99%